Between Sepharad and Jerusalem : history, identity and memory of the Sephardim - Meyuhas Ginio, Alisa, 1937- (Iberian religious world, 2014)
The history, identity and memory of the Sephardim in their Mediterranean dispersal are analysed by the author with a special reference to the Sephardi community of Jerusalem and to the political, social and cultural changes through which the speakers of Jewish-Spanish went since the turn of the nineteenth century.